2021
DOI: 10.1007/s10290-021-00434-1
|View full text |Cite
|
Sign up to set email alerts
|

Bank liquidity creation: A new global dataset for developing and emerging countries

Abstract: Benchmarking IFS data with national data sources is not always possible. As highlighted by Jerven (2016), some DECs adopt the IMF reporting standards for their domestic data collections; some other jurisdictions, however, use the IMF definitions and reporting standards only for reporting to the IMF while keeping a different official reporting domestically. That is, from a practical viewpoint, balance sheet banking data from national sources does not allow for cross-country comparison due to the lack of harmoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Despite the extensive empirical evidence, few studies in developing countries have been explored (see for example, Kusi et al ., 2021; Abraheem et al ., 2020; D’avino et al ., 2022; Umar et al ., 2018; Yahaya et al ., 2021). In Kenya, Nyaundi (2015) investigated the impact of capital adequacy requirements on Kenyan commercial banks' liquidity, but did not pay attention to liquidity creation.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Despite the extensive empirical evidence, few studies in developing countries have been explored (see for example, Kusi et al ., 2021; Abraheem et al ., 2020; D’avino et al ., 2022; Umar et al ., 2018; Yahaya et al ., 2021). In Kenya, Nyaundi (2015) investigated the impact of capital adequacy requirements on Kenyan commercial banks' liquidity, but did not pay attention to liquidity creation.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…For instance, Da'vino et al. (2021) examined LC by banks in developing and emerging economies for the period pre‐ and post‐crisis of 2008. They found that there was a sharp pre‐crisis build‐up in LC by banks in developing economies to an extent that was larger than in developed countries, but there was a post‐crisis fall in LC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Berger and Bouwman (2017) underscored the prevalence of high LC before the financial crisis. Such potential ramifications have led economists to explore the relationship between LC and banks’ characteristics, such as capital, financial stability and competition, in developed countries (e.g., Berger and Bouwman, 2009; Fungacova et al., 2010; Berger et al., 2016) as well as developing countries (Davino et al., 2021; Umar and Sun, 2016a, 2016b; Dahir et al., 2018; Dang and Dang, 2021). These significant implications of LC nudge us to examine the case of monetary policy transmission to LC in India.…”
Section: Introductionmentioning
confidence: 99%
“…The nancial intermediation role of banks enhances capital ow and liquidity to nance entrepreneurial activities and in the long run promote social welfare (Zheng et al 2019; Khan et al 2020; Baradwaj et al 2016). Thus, the major channel through which banks may in uence economic development is liquidity creation (Wang et al, 2022;D'avino, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%